Instagram-based Learning Media and Chemistry Practicum Video Projects to Improve Students’ Creative Thinking Skills - Cindy Nur Anggreani; Sri Yamtinah; Endang Susilowati; Ari Syahidul Shidiq; Hayuni Retno Widarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Chemistry is considered a complex subject because of its abstract nature. In addition, its relation to everyday life requires a greater understanding of concepts such as reaction-rate material. One way to overcome this problem is to use an appropriate learning model involving students actively developing their ideas, such as the STEM-integrated project-based learning model. Instagram learning media has the most potential to be used as learning media in project-based learning. This research aims to improve students' creative thinking skills through chemistry lab video projects on Instagram. The method used in this study was quasi-experimental with a pretest-posttest nonequivalent control group design. The sample was from science class in elevent garade students. Based on the result of the hypothesis testing, it shows that there is a significant difference in the use of practicum video projects on Instagram in the STEM integrated project-based learning model (STEM-PjBL) on students' creative thinking skills. This practicum video on Instagram can be an opportunity to improve students' creative thinking skills.